Dual functionalized task specific ionic liquid promoted in situ generation of palladium nanoparticles in water: synergic catalytic system for Suzuki–Miyaura cross coupling1. Issue 96 (17th October 2015) - Patil, Jayavant D.; Korade, Suyog N.; Patil, Supriya A.; Gaikwad, Dipak S.; Pore, Dattaprasad M.
<x xml:space="preserve">Abstract</x> A new task specific ionic liquid with hydroxyl and prolinate functionalities acts as a reducing agent and serves as a ligand and stabilizer for in situ formed palladium nanoparticles. This system displays high catalytic activity for Suzuki–Miyaura cross-coupling in water.